Access Rights to Health Services for Tolotang Believers as Minority Group, Sidrap District, Indonesia - Iin Karita Sakharina; Aidir Amin Daud; Hamzah Halim; Muh. Hasrul; Wahyudi Pratama; Sukri Palutturi; Anif Laila Sahir (Indian Journal of Forensic Medicine & Toxicology, 2021)
The purpose of this paper was to analyze the forms of protection and fulfillment of human rights by localgovernments against the followers of the Tolotang faith in accessing their right to health service as minoritygroup in Sidenreng Rappang District, South Sulawesi Province. The type of research used was normativelegal research using a statutory approach. The results showed that The followers of the Tolotang faith havebeen recognized by the state, and weregiven space to worship based on their beliefs. Also Tolotang faithhave recognize by the local goverment as part of the community in Sidenreng Rappang who have the sameaccess in order to get health service from any medical stuff, doctor, clinic , hospital whenever they needit.The findings of this article can provide insights into the forms of protection and fulfillment of humanrights by local governments against the followers of the Tolotang faith inin in accessing their right to healthservice as minority group in Sidenreng Rappang District, South Sulawesi Province.The followers of theTolotang faith have been recognized by the state, and weregiven space to worship based on their beliefs.Also Tolotang faith have recognize by the local goverment as part of the community in Sidenreng Rappangwho have the same access in order to get health service from any medical stuff, doctor, clinic , hospitalwhenever they need it.